2004
DOI: 10.1103/physrevb.70.014428
|View full text |Cite
|
Sign up to set email alerts
|

Orbital degeneracy as a source of frustration inLiNiO2

Abstract: Motivated by the absence of cooperative Jahn-Teller effect and of magnetic ordering in LiNiO2, a layered oxide with triangular planes, we study a general spin-orbital model on the triangular lattice. A mean-field approach reveals the presence of several singlet phases between the SU(4) symmetric point and a ferromagnetic phase, a conclusion supported by exact diagonalizations of finite clusters. We argue that one of the phases, characterized by a large number of low-lying singlets associated to dimer coverings… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
106
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(107 citation statements)
references
References 28 publications
1
106
0
Order By: Relevance
“…Pati et al have shown that this dimerized phase extends to a very large portion of the phase diagram around this point. From that point of view, the identification of dimer phases in the context of spin-orbital models of BaVS 3 [29] and of LiNiO 2 [24] is not unexpected, and the tendency to dimerize can be considered to be a generic trend of spin-orbital models. What seems to be more specific to these spin-orbital models of LiNiO 2 and BaVS 3 is the quasi-degeneracy of all nearest-neighbour dimer coverings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pati et al have shown that this dimerized phase extends to a very large portion of the phase diagram around this point. From that point of view, the identification of dimer phases in the context of spin-orbital models of BaVS 3 [29] and of LiNiO 2 [24] is not unexpected, and the tendency to dimerize can be considered to be a generic trend of spin-orbital models. What seems to be more specific to these spin-orbital models of LiNiO 2 and BaVS 3 is the quasi-degeneracy of all nearest-neighbour dimer coverings.…”
Section: Discussionmentioning
confidence: 99%
“…A fairly general description of this system is given by a Kugel-Khomskii Hamiltonian defined in terms of Wannier functions centered on the Ni sites by two hopping integrals t h and t ′ h , the on-site Coulomb repulsion U and the Hund's coupling J which, on a given bond, takes the form [24] …”
Section: Microscopic Modelmentioning
confidence: 99%
“…The lack of obvious orbital ordering in LiNiO 2 and the orbital degeneracy which would arise in its absence has motivated many theoretical authors to consider coupled orbital and spin degrees of freedom 7,8,9,18,19,20,21 as a mechanism to suppress magnetic ordering at low temperatures. Other recent work suggests orbital and spin degrees of freedom are decoupled 14 .…”
Section: Materials and Experimental Methodsmentioning
confidence: 99%
“…5 In spite of this, LiNiO 2 still remains interesting because of the absence of a cooperative Jahn-Teller distortion that is expected for such a system with orbital degeneracy. 6 Experimental results on LiNiO 2 are rather controversial. It always suffers from nonstoichiometry: excess Ni ions replace Li ions, which gives rise to a local interlayer FM coupling that competes with an intrinsic AFM coupling.…”
mentioning
confidence: 99%